The Rhetorical Patterns of Argumentative Compositions of the English Department Students of Widya Mandala Catholic University Surabaya - Liza Stephanie (Magister Scientiae, 2009)
This study is intended to reveal the rhetorical patterns frequently found in the students’ argumentative compositions of the English Department of Widya Mandala Catholic University Surabaya specifically to the Classical Model of Argument. The data were taken from their final exam papers the students of the English Department of Widya Mandala Catholic University Surabaya who took Writing 3. The analysis showed that only two of the students’ compositions were truly linear. The other compositions were linear but with incomplete evidence in the conclusion, and linear with indirect conclusion. It can then be concluded that all students under study had not mastered the Plato- Aristotelian style of writing especially to the Classical model of argument quite well.